Virtuous testimonial belief in young children. Issue 3 (3rd July 2019) - Ryan, Shane
Abstract : I lay out the challenge posed by testimonial knowledge in young children to virtue reliabilist accounts of knowledge. In particular, I examine accounts from Greco and Pritchard and argue that those accounts are too demanding. More specifically, I make the case that young children can have testimonial knowledge without meeting the ability requirements claimed by Greco and Pritchard. As a virtue theoretic alternative, I argue that an agent's belief must be epistemically virtuous, but that this may sometimes involve belief from a trait rather than an ability.